Organizational Principles Of The Use Of Forensic DNA Analysis In The Investigation Of Criminal Offenses Organizational Principles Of The Use Of Forensic DNA Analysis In The Investigation Of Criminal Offenses - Stepaniuk , Daria (Archives of Criminology and Forensic Sciences, 2023)
This article studies organizational principles of forensic DNA analysis as the area of practical activities in the field of detection and investigation of criminal offenses. The author defined the list of organizational principles of forensic DNA analysis, disclosed their content, and determined the conditions for implementation in Ukraine. It was established that these principles are: legality, that is, strict compliance with the requirements of the law at all stages of collecting and researching biological material, using and storing genomic information; an exclusively procedural form of using DNA analysis in criminal proceedings; proper functioning of forensic accounting of human genomic information; formation of DNA analysis as a separate section of forensic technology; its organizational and technical support, which primarily involves the accreditation of forensic genetics laboratories according to the European quality standard and compliance with the conditions regarding technical equipment and personnel support. It is substantiated that the implementation of these principles necessitates the need to take a number of regulatory and organizational measures at the national level to ensure at least the minimum conditions for the effective use of forensic DNA analysis technologies, namely: to improve legal norms at least in the aspect of regulation of procedures for obtaining biological material, management of DNA databases and protection of genomic information; determine exclusively the procedural form of using DNA analysis in the criminal process, regulating, in addition to molecular genetic examination, verification studies; to intensify scientific research in the field of criminalistics in the direction of DNA analysis and to introduce relevant topics into educational programs for the training of lawyers and law enforcement officers; to coordinate the work of various DNA analysis laboratories in the context of their accreditation, technical equipment with compatible equipment and personnel training.